The role of miR-200b/c in balancing EMT and proliferation revealed by an activity reporter - Gollavilli, Paradesi Naidu; Parma, Beatrice; Siddiqui, Aarif; Yang, Hai; Ramesh, Vignesh; Napoli, Francesca; Schwab, Annemarie; Natesan, Ramakrishnan; Mielenz, Dirk; Asangani, Irfan Ahmed; Brabletz, Thomas; Pilarsky, Christian; et al. (Oncogene, 2021)
Since their discovery, microRNAs (miRNAs) have been widely studied in almost every aspect of biology and medicine, leading to the identification of important gene regulation circuits and cellular mechanisms. However, investigations are generally focused on the analysis of their downstream targets and biological functions in overexpression and knockdown approaches, while miRNAs endogenous levels and activity remain poorly understood. Here, we used the cellular plasticity-regulating process of epithelial-to-mesenchymal transition (EMT) as a model to show the efficacy of a fluorescent sensor to separate cells with distinct EMT signatures, based on miR-200b/c activity. The system was further combined with a CRISPR-Cas9 screening platform to unbiasedly identify miR-200b/c upstream regulating genes. The sensor allows to infer miRNAs fundamental biological properties, as profiling of sorted cells indicated miR-200b/c as a molecular switch between EMT differentiation and proliferation, and suggested a role for metabolic enzymes in miR-200/EMT regulation. Analysis of miRNAs endogenous levels and activity for in vitro and in vivo applications could lead to a better understanding of their biological role in physiology and disease.
CRIS-Team Scopus Importer:2021-03-19